Determinan Return on Assets pada Sektor Konsumer Non-Cyclicals: Firm Size, Firm Age, Leverage dan Liquidity - Nichelle Wahyudi; Amin Wijoyo; Nastasya Cindy Hidajat (Jurnal Multidisiplin Indonesia, 2026)
This study investigates whether firm size, firm age, leverage, and liquidity influence the financial performance of consumer non-cyclicals companies, with Return on Assets (ROA) serving as the performance indicator. The study focuses on consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. A quantitative research approach was employed using secondary data obtained from the companies’ annual financial reports. The sample was selected through purposive sampling, resulting in 60 companies with a total of 180 observations over the three-year period. Panel data regression analysis was conducted using EViews 14 and Microsoft Excel to examine the relationships between the independent variables and financial performance. The findings indicate that firm age has a positive and significant effect on ROA, suggesting that companies with longer operational experience tend to achieve better financial performance. Conversely, leverage has a significant negative effect on ROA, indicating that higher debt levels reduce profitability due to increased financial obligations. Meanwhile, firm size and liquidity do not significantly affect ROA, implying that larger asset ownership and higher liquidity levels do not necessarily improve financial performance in the consumer non-cyclicals sector. These findings highlight the importance of maintaining prudent debt management while leveraging accumulated operational experience to enhance profitability. The study provides practical implications for corporate management and investors in evaluating financial performance and making strategic business decisions within the consumer non-cyclicals industry.